Marketing in the participation age : a guide to motivating people to join, share, take part, connect, and engage - Middleton, Daina (Hoboken, NJ : John Wiley & Sons Inc., 2013)
'Turn intrinsic human desires into your most powerful marketing tool. Marketing in the Participation Age shows you how to rethink marketing. Transform consumers into active participants for your brand by capturing their interest, empowering them to contribute, and developing meaningful relationships that keep them involved. Learn how to create a marketing environment that fulfills your customers' desire to seek challenges and discover new things--and watch their participation yield greater revenues for your business.'--Publisher's website.
Introduction: The Participation Age -- Marketing in the Age of Participation -- The Catalyst: The Consumer-to-Participant Transformation -- Tools for the Past 60 Years -- Time for a Participation Revolution -- Participation Way for the Participation Age -- D + E + C = P2: Discover -- D + E + C = P2: Empower -- D + E + C = P2: Connect -- D + E + C = P2: Participation -- D + E + C = P2: Performance -- Planning: Bringing the Participation Way to Life -- Measuring Participation Performance -- The Future Marketer: The Nurturist.
Includes bibliographical references (p.195-197) and index.
Keywords: Marketing